The effect of body mass index and position on blood surface area on sanitary pads - Siska Febrina Fauziah; Viqy Lestaluhu; Imas Kurniawati; Dita Eka Mardiani; Helmi Diana (Institute of Computer Science (IOCS), 2025)
Accurate measurement of postpartum blood loss is crucial for guiding appropriate medical interventions. Digital image processing offers potential to enhance visual estimation accuracy, though refinement is still needed for sanitary pad media. This study examined the effect of body mass index (BMI) and body position on the blood surface area on sanitary pads to support the development of digital image-based measurement methods. An experimental design simulated postpartum blood loss using three BMI categories (underweight, normal, overweight) and three positions (sitting, side-lying, supine), each repeated twice. Blood surface area was measured using digital image processing and analyzed with the Kruskal-Wallis and Friedman tests. The sanitary pads’ absorption capacity ranged from 70–80 mL. Blood surface area did not differ significantly by BMI (p=0.597) but varied significantly by position (p=0.000). A trend of increasing surface area with higher BMI was observed. These findings suggest that both BMI and position should be considered in refining digital image-based methods for accurate and objective postpartum blood loss measurement.